Assessment of three decades treated wastewater impact on soil quality in semi-arid agroecosystem - Ibrahimi, Khaled; Attia, Kmar Ben; Amami, Roua; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Sher, Farooq (Springer Nature, 2022)
The use of treated wastewater (TWW) for crop irrigation is practiced in many countries worldwide as a strategy to offset water scarcity. Soil quality assessment is required to ensure that the application of this non-conventional irrigation water is sustainable over long periods. A relatively limited number of studies have used soil quality indexing approaches to investigate the impacts of TWW irrigation on soil quality. Therefore, this study aimed to assess the impacts of more than three decades of TWW irrigation on Fluvisol in semi-arid agrosystem to develop soil quality indices and evaluate their use as a practical tool to support TWW irrigation management. Overall, a total of 13 key soil attributes, used as soil quality indicators, were monitored in three TWW-irrigated plots and their adjacent non-irrigated control in eastern Tunisia. These selected indicators were used to develop a soil quality index (SQI) based on either a total data set (SQI-TDS) or a minimum data set (SQI-MDS) indexing approach. In comparison to the control, TWW application significantly increased saturated hydraulic conductivity (Ks) (+740%), saturation percentage (SP) (+20%), aggregate stability (AS) (+64%), field capacity (FC) (+52), electrical conductivity (EC) (+72%), phosphorous (P) (+472%), potassium (K) (+43%), organic matter (OM) (+90%) and basal respiration (BMR) (+117%) and decreased hydrophobicity (−17%), bulk density (BD) (−13%), cone penetration resistance (CPT) (−17%) and pH (−4%). The two developed SQI-TDS and SQI-MDS indices were sensitive to distinguish the impacts of TWW irrigation on soil quality in the study area. In comparison to the control, the TWW-irrigated soils exhibited higher SQI ratings by 42 and 52% based on SQI-MDS and SQI-TDS, respectively. Based on the monitored soil quality indicators in TWW-irrigated and control plots, this study indicates that long-term TWW application improved the overall soil quality and supports SQI-MDS's efficiency in providing an adequate evaluation of soil quality in the study area.
Keywords: Green agriculture; Indexing approach and Fluvisol; Indices; Soil quality; Sustainable environment; Treated wastewater